2017
DOI: 10.1007/s11252-016-0637-y
|View full text |Cite
|
Sign up to set email alerts
|

How small cities affect the biodiversity of ground-dwelling mammals and the relevance of this knowledge in planning urban land expansion in terms of urban wildlife

Abstract: Fundamental principles regarding urban biodiversity are based on studies conducted in large cities. However we cannot know whether the same phenomena occur in smaller cities or how small cities affect biodiversity. Small cities are an inherent element of urbanization and in the future, most global urban growth is expected to take place in small and mediumsized cities. Understanding the effects of small cities on biodiversity will be an important aspect in planning urban land expansion. Our study examined the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…In contrast to anthropogenic resources, the consumption of small mammals was positively associated with the proportion of agricultural land and negatively associated with the extent of urbanisation. This finding may be explained by regional differences in prey availability, which is consistent with our prediction, as it has previously been shown that the richness and diversity of small rodents is elevated in agricultural landscapes (Delattre et al 1996, Alain et al 2006, Panazacchi et al 2010 and reduced in urban areas (Cavia et al 2009, Łopucki & Kitowski 2017. However, we could not find any similar patterns in the consumption of other natural foods, despite faunal and floral richness and diversity generally showing similar responses to landscape modification (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to anthropogenic resources, the consumption of small mammals was positively associated with the proportion of agricultural land and negatively associated with the extent of urbanisation. This finding may be explained by regional differences in prey availability, which is consistent with our prediction, as it has previously been shown that the richness and diversity of small rodents is elevated in agricultural landscapes (Delattre et al 1996, Alain et al 2006, Panazacchi et al 2010 and reduced in urban areas (Cavia et al 2009, Łopucki & Kitowski 2017. However, we could not find any similar patterns in the consumption of other natural foods, despite faunal and floral richness and diversity generally showing similar responses to landscape modification (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…These considerations suggest that such antagonistic interspecific episodes can potentially increase corticosterone levels in the studied animals living in multispecies communities. In contrast to rural areas, in urban sites the pressure of competitors is much lower, as is evident in our results and in the literature (Andrzejewski et al 1978;Łopucki et al 2013;Łopucki and Kitowski 2017), therefore there are fewer antagonistic interspecific episodes. An unanswered question relates to the competitive relationship between the striped field mouse and brown rats Rattus norvegicus in urban areas, in which the mouse is apparently in a subordinate position.…”
Section: Factorsupporting
confidence: 81%
“…The study was carried out in the city of Chełm (51°07′ N, 23°28′ E), Poland, Europe. The city has an area of 35.5 km 2 , a population of 65,643, 160 km of paved roads, and over 55,000 registered vehicles (in 2018–2020) [ 24 ]. Small cities are much more common than large cities (in number and total occupied area), and almost half of the world’s urban population lives in small cities [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%